Religious Values (Sincerity) in the Poem of Dīwān Al-Imām Al-Shāfi'i and Its Influence on Character Education - Muhajir, Mohamad; Mohamad Syukri; Khairatul Akmar; Saifulah Samsudin (Maharaat: Jurnal Pendidikan Bahasa Arab, 2025)
This study aims to examine the value of sincerity as a basis for character education through the analysis of the verses in Dīwān al-Imām al-Shāfi'i. The approach used is qualitative with a thematic analysis method, which focuses on identifying, coding, and categorizing the themes of sincerity contained in the poetry text. The research data is in the form of verses that represent the concept of sincerity, such as sincerity of intention, orientation of worship to Allah, attitude of zuhud, and avoidance of riya' and worldly interests. The analysis process is carried out through the stages of data familiarization, open coding, theme formation, and interpretation of meaning in the context of character education. The results of the study show that the value of sincerity in Dīwān al-Imām al-Shāfi'i is manifested in several main themes, namely: (1) sincerity as the foundation of charity, (2) purity of intention in seeking knowledge, (3) tawakal attitude and dependence on Allah, and (4) rejection of worldly motivation in charity. These values have significant relevance in the formation of students' character, especially in instilling integrity, moral responsibility, and spiritual orientation in the educational process. This study concludes that sincerity is not only a theological value, but also has a strong pedagogical dimension as the basis for character education. Therefore, the integration of the value of sincerity sourced from classical works such as Dīwān al-Imām al-Shāfi'i can be a strategic alternative in strengthening character education in the modern era that tends to be materialistic.